(3Gdbhd GdeajO aj Gdfjd GdSYjOs - (3CMeO Hf YeGO Hf jhSa Hf YHO GdfHj, CHh GdYHGS, TgGH GdOjf GdCbagSj Ke GdbGgQj , GHf GdpYneGO ,J (B808 (3g` s
(3ChdgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B( (3CQHYI dGJTHY ef GQHY Yjf ef fXQ hGfKi ef PcQ hCQV ef eWQ hYGde ef NHQ (B) s
(3BNQgG (B:s
(3Ef JMJ GdHMQ dfGQ hEf JMJ GdfGQ dHMQ (B" (3GdMOjK (B" s
(3HgG fXGe GdJYbjHIs
(3ai fgGjJg OYGA NJe TQja hHYV GdCOYjI GdCNQis
(3fSNI KGdKI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdLZQGajG h GdHdOGfs